Urine Stem Cells: A Novel Insight - Talati, Meenakshi; Shah, Rohit; Avachat, Tejashree; Mitra, Dipika; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
Stem cells are a class of undifferentiated cells that are able to differentiate into specialized cell types that have capacity to serve any function making them powerful enough to regenerate damaged tissue under right conditions. Stem cells commonly come from 2 main sources: 1. Embryo(Blastocyst) 2. Adult tissue (Adult Stem Cells)